Diarrhea Prevention and Treatment Counseling In Suka Maju Village, Penarik District, Mukomuko Regency - Dewi Suparti; Situmorang, Emma Carolina; Hasugian, Reditta; Situmorang, Ronalen; Diniarti, Fiya (Jurnal Inovasi Kerja Nyata, 2025)
Diarrhoea is usually caused by a virus or, sometimes, food contaminated by bacteria. It is rarely a sign of other disorders, such as inflammatory bowel disease or irritable bowel syndrome (Febriyanti and Triredjeki, 2021). According to WHO and the United Nations Children's Fund (UNICEF), there are approximately two billion cases of diarrhoeal disease worldwide each year, and 1.9 million children under the age of 5 die from diarrhoea. Of all child deaths from diarrhoea, 78% occur in Southeast Africa and the Asian region (World gastroentorology Organisation, 2020). January the number of patients suffering from diarrhoea was 70 patients, rising to 84 patients in February, an increase of 14%. (WHO, 2020). Based on the PISP Report Data Recap UPTD Puskesmas Penarik in 2024, there were 6 cases of diarrhoea from RT 04 Suka Maju Village out of a total of 32 cases of diarrhoea in the UPTD Puskesmas Penarik Working Area. This should certainly be a concern because according to WHO diarrhoea is the third cause of death in children aged 1-59 months. This disease can be prevented and treated, one of which is by washing hands effectively after every activity. This Community Service through KKN-T is a form of community service that aims to improve the knowledge, awareness and behaviour of the community of RT 04 Suka Maju Village about the prevention and treatment of diarrhoea. The program was carried out through educational methods, hand washing campaign practices and Gotong Royong implementation of Clean and Healthy Living Behaviour (PHBS) which was carried out at Integrated Paud Desa Suka Maju Kec. Penarik Kab. Mukomuko Bengkulu with the target of Paud children, teachers, and mothers of toddlers totalling 44 people. The community has received information about the causes, signs and symptoms, prevention and treatment of diarrhoea and how to wash hands effectively and the community together participated in gotong royong cleaning the school environment for the implementation of PHBS. The results of this activity showed an increase in community knowledge and awareness about diarrhoea, prevention and application of effective hand washing and PHBS for diarrhoea prevention efforts in Suka Maju village. It is hoped that the community can implement clean and healthy living behaviour.